The Single Supervisory Mechanism in the context of a European Banking Union under construction: bridging the Euro debt crisis with defences designed for the future - Carmo, Rui do (UNIO – EU Law Journal, 2018)
Set up in the past few years under the shadow of the Euro debt crisis, the European Banking Union (EBU) has been taking its first steps, aiming to prevent the dreaded repetition of the recent shortcomings of the several components of the European Monetary Union (EMU). By revisiting some specific events that led to the Euro crisis, this paper seeks to provide some insights on the understanding of the set-up of the Single Supervisory Mechanism (SSM), in the context of the broader conjunction of the several instruments put forward to provide the EBU with the resilience to prevent future crises. The text provides a brief background of the events that triggered the need for setting up the EBU, followed by an overview of its different constitutive elements and, finally, a critical analysis of the most prominent aspects of the SSM.